Migration and Remittances : Recent Developments and Outlook - World Bank (Washington, DC, 2017)
Remittances to developing countries are projected to grow by 5.0 percent to reach US$435 billion in 2014 (accelerating from the 3.4 percent expansion of 2013), and rise further by 4.4 percent to US$454 billion in 2015. In 2013, remittances were more than three times larger than ODA and, excluding China, significantly exceeded foreign direct investment flows to developing countries. Growth of remittances in 2014 is being led by three regions: East Asia and the Pacific, South Asia, and Latin America and the Caribbean.